Integration Of Digital Twin Technology and Smart Sensors in Real-Time Monitoring of Structural Health (SHM) of High-Rise Buildings - Rahmawati; Amiruddin. A; Nicodemus Rahanra; Mira Wellya Fatma; Wahyudin (Yayasan Inovasi Kemajuan Intelektual, 2025)
The integration of Digital Twin (DT) technology and smart sensors represents a new paradigm in structural health monitoring (SHM) of high-rise buildings. This study explores the synergy between data-driven physical simulation and real-time data collection to improve the accuracy of early damage detection. Using wireless sensor networks integrated with Building Information Modeling (BIM) models, environmental load and structural response data are processed in real time. The analysis results show that DT can reduce the margin of error in structural failure prediction by up to 30% compared with conventional methods. This study concludes that bidirectional data synchronization between the physical and digital worlds is crucial for disaster risk management and the efficient maintenance of modern buildings in dense urban areas.